Sanctioning regime in public procurement in contraposition of minimum guarantees foreseen in the sanctioning regime of Unique Ordered Text of the General Administrative Procedure Law of Peru - Terrones Jancco, Jhojan (2020)
This paper explains the legal nature of the administrative power to impose sanctions, and how the OSCE Contracting Court acts based on this power. Likewise, it calls for a deep legal reflection, insofar as the sanctioning regime in the field of public procurement violates any of the minimum guarantees provided for in the TUO of Law No. 27444, Law on General Administrative Procedure.